Denosumab is effective in the treatment of bone marrow oedema syndrome. Issue 4 (April 2017) - Rolvien, Tim; Schmidt, Tobias; Butscheidt, Sebastian; Amling, Michael; Barvencik, Florian
Abstract: Bone marrow oedema (BMO) syndrome describes a painful condition with increase of interstitial fluid within bone and is often lately diagnosed due to unspecific symptoms. The underlying causes are diverse while it is widely assumed that in cases of BMO local bone resorption is increased. Denosumab, a human monoclonal antibody that binds to the receptor activator of nuclear factor kappa-B ligand (RANKL) inhibits osteoclastic bone resorption and is commonly administered in the treatment of osteoporosis. Besides one previous case report, its clinical effectiveness in the treatment of bone marrow oedema has not been elucidated. We treated 14 patients with primary (idiopathic) bone marrow oedema of the lower extremity with single dose denosumab application. Mean time between onset of pain and therapy was 155 days. MRI scans were performed for initial diagnosis, and 6–12 weeks after denosumab injection. Vitamin D and calcium homeostasis were strived to be balanced before initiation of therapy. Furthermore bone status was analysed using Dual-energy X-ray absorptiometry (DXA) and extended bone turnover serum markers. After 6–12 weeks, BMO dissolved partly or completely in 93%, while a complete recovery was observed in 50% of the individuals. Visual analogue scale (VAS) evaluation revealed a significant decrease in pain level. Furthermore, bone turnover decreased significantly after treatment. No adverse reactions were reported. In conclusion, our retrospective analysis shows that denosumab is highly effective in the treatment of bone marrow oedema and therefore represents an alternative treatment option.